Fitopatología 2.0, aprender sin coincidir en el tiempo y el espacio: una alternativa metodológica para la enseñanza de la Fitopatología - Alcalde, Mónica Adriana (2017)
The inclusion of ICTs in education has produced a genuine pedagogical revolution. It is not a question of incorporating new technologies in the service of traditional teaching models, with content-transmitting teachers and students who are recipients of it, and rigid organizations of space and It has become necessary to innovate in pedagogical conceptions and practices, developing more open and flexible teaching-learning models, transforming the ways, forms and times of interaction between teachers and students, favoring their collaboration and autonomy in the Their learning. In this context ICTs are an ideal instrument for the creation of virtual learning environments that integrated to the classroom environments raise the quality of education. It is not a question of replacing the classroom class but of complementing it and that is why in this work a pedagogical-didactic proposal mediated by ICT was developed, based on an endogenous communication model with a didactic design of socio-constructivist character, integrated to the space Educational at the university, for teaching and learning Phytopathology. It is an innovative methodological resource that allows the student to learn without coinciding in time and space.